Prevalência do Papiloma Vírus Humano (HPV) na cavidade oral, orofaringe e colo do útero em mulheres de Juazeiro do Norte, Ceará, 2023 - Santos, Matheus Moura dos (2024)
The Human Papilloma Virus (HPV) is studied worldwide due to its association with cancer, particularly cervical cancer, which has a high prevalence among women in developing countries such as Brazil. Molecular studies on cancers of the oral cavity and oropharynx reveal the presence of HPV DNA in these tumors, demonstrating its involvement in oral carcinogenesis. More than 200 types of HPV have been identified and genetically sequenced. The virus genotypes are classified according to their oncogenic potential, and can be low-risk or high-risk.The main objective of this study was to estimate the prevalence of HPV infection and its genotypes in women from the municipality of Juazeiro do Norte, Ceará. This is an analytical cross-sectional study. The study involved 166 women who were at the clinics for their preventive gynecological examination (Pap smear). They were informed about the research, asked to sign an informed consent form, and had their samples taken. Samples were collected from three anatomical sites in each participant: jugal mucosa, oropharynx, and cervix. HPV was detected and genotyped using multiplex nested PCR with primers that amplify the intergenic region and detect genotypes 6, 11, 16, 18, 31, 33, 45, 52, 56, 58, and 59. Statistical analyses were conducted using R software and Excel.In the oropharynx survey, 26 participants tested positive for E6/E7 (18.0%). The most prevalent genotype was HPV 16, found in 11.1% of participants. Other identified types included HPV 33, HPV 52, HPV 56, HPV 58, and HPV 59. In the jugal mucosa, 27 participants (18.5%) tested positive for E6/E7. HPV 52 was the most prevalent specific type, found in 8.9% of participants, followed by HPV 16, present in 7.5%. Other identified types included HPV 58, HPV 33, HPV 56, and HPV 6/11.In the E6/E7 test of the cervix, 27 participants (17.8%) tested positive. Regarding the HPV types identified, HPV 52 was the most prevalent, found in 9.9% of participants. Other identified types included HPV 16, HPV 58, HPV 33, HPV 56, and HPV 6/11.When examining the presence of HPV in the cervix in relation to its detection in the oral region, we found that 52.8% of the participants who tested positive for HPV in the cervix also tested positive for HPV in the oral region. Conversely, among those who tested negative for HPV in the oral region, 38.9% were positive for HPV in the cervix. The groups of women who tested positive for HPV in both the cervix and oral mucosa or oropharynx were compared with the collected variables. Single women had a significantly higher proportion of HPV in the jugal mucosa, oropharynx, and cervix (38.6%) compared to married women (20.4%). The odds ratio (OR) was 2.45 (95% CI: 1.22 - 4.92).The prevalence of HPV in the anatomical sites studied in the women from Juazeiro do Norte was similar to that observed in Brazil and worldwide. The three most frequent genotypes in the oropharynx, jugal mucosa, and cervix of the participants were HPVs 16, 52, and 58.